Anti-inflammatory therapy for tendinopathy using Il1rn mRNA encapsulated in SM102 lipid nanoparticles - Zhang, Yuan; Li, Xu; Li, Hao; Zhang, Ruiyang; Zhang, Ti; Juma, Talante; Zhou, Yongfei; Guo, Quanyi; Zhao, Hui; Cao, Yongping (Frontiers in Bioengineering and Biotechnology, 2025)
Tendinopathy treatment is hindered by persistent inflammation and irreversible matrix degradation, with current therapies offering transient symptom relief without addressing disease progression. Here, we developed an mRNA-based anti-inflammatory strategy utilizing SM102 lipid nanoparticles (LNPs) to deliver interleukin-1 receptor antagonist (Il1rn) mRNA for tendon repair. SM102-LNPs demonstrated efficient transfection of primary tendon stem cells, sustaining IL-1RA protein expression for over 72 h and neutralizing IL-1β-induced inflammatory cascades. In vitro, IL-1RA suppressed pro-inflammatory cytokines (TNF-α, IL-6, iNOS), restored collagen I/III balance, and enhanced cell migration. In collagenase-induced tendinopathy mice, a single SM102-Il1rn mRNA injection attenuated inflammation, reduced MMP1/13 expression, and improved collagen alignment within 1 week. By 4 weeks, treated tendons exhibited functional recovery with normalized gait patterns. Transcriptomics revealed dual modulation of IL-1 signaling and extracellular matrix (ECM) remodeling pathways, alongside macrophage polarization and oxidative stress regulation. Systemic safety was confirmed by unaltered serum biomarkers and organ histology. This SM102-Il1rn mRNA therapy enables spatiotemporally controlled anti-inflammatory therapy, providing a promising non-surgical solution for refractory tendinopathies. Its adaptable design allows expansion to other regenerative targets, advancing precision treatment for musculoskeletal degeneration.